A minimal model for forest fire regimes - Renato Casagrandi; Sergio Rinaldi (Fondazione Eni Enrico Mattei (FEEM), 1998)
We show in this paper how the characteristics of fire recurrence in forests can be theoretically derived from simple information concerning forest morphology. The task is accomplished by means of a minimal model encapsulating a few assumptions on the interactions between overstorey and understorey species and on the mechanisms of fire development and transmission. The main difference with other models for fire prediction and simulation is that, here, fire is an endogenous variable with purely deterministic dynamics. Nevertheless, the analysis shows that fire recurrence can be chaotic for parameter values corresponding to Mediterranean forests. By contrast, the model shows that boreal forests and savannahs must experience periodic fires. These general results are in agreement with the studies carried out on many different forests in this century.
Keywords: 330; Wald; Brand; Theorie